Acceleration of Organic Compost Supply Using Microbial Consortium Formulation on Various Organic Wastes and their Effect on Sweet Corn: Acceleration of Organic Compost Supply Using Microbial Consortium Formulation - Tyasmoro, Setyono Yudo; Saitama, Akbar; zulfikar, Aji (Journal of Tropical Life Science, 2024)
Organic waste, primarily originating from agricultural sources, remains underutilized in Indonesia, despite its substantial potential as an organic fertilizer. Consequently, it is imperative to comprehend the technology capable of efficiently decomposing organic matter and yielding high-quality compost. This study aimed to investigate the impact of a microbial consortium comprising Bacillus sp., Pseudomonas sp., Trichoderma sp., and Aspergillus sp. on the decomposition of organic waste derived from rice, sugarcane, corn and as well as to examine its application to sweet-corn (Zea mays var. saccharata). The study used a factorial randomized block design, featuring two primary factors, compost types and their respective doses. This design in total of nine treatments, each replicated three times, thus resulting in a sum of 27 experimental units. The treatments were RSC: Rice straw compost; SLC: Sugarcane leaves compost; CHC: Corn husk compost; D7.5: Compost dose of 7.5 t ha-1; D15: Compost dose of 15 t ha-1; D22.5: Compost dose of 22.5 t ha-1.  Moreover, an essential fertilizer, NPK, was applied at a rate of 200 kg/ha. The findings demonstrated a substantial impact of both compost types and doses on maize growth parameters, which encompassed plant height, leaf area, chlorophyll contentand dry weight. These effects were observed individually, without any interactions between the two factors. Furthermore, these treatments exhibited a discernible influence on corn yield. The highest to lowest yields were recorded as follows: CHC (9.29 t ha-1), RSC (8.72 t ha-1), and SLC (8.00 t ha-1). Combining organic compost with chemical fertilizer effectively prevented nutrient loss through denitrification and evaporation, facilitating nutrient retention and controlled release over time.